Characterization and expression of Cm-AAT1 gene encoding alcohol acyl-transferase in melon fruit (Cucumis melo L.) ‘Hikapel’ - WIKO ARIF WIBOWO; MUHAMMAD IMAM FATKHUROHMAN; BUDI SETIADI DARYONO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wibowo WA, Fatkhurohman MI, Daryono BS. 2020. Characterization and expression of Cm-AAT1 gene encoding alcohol acyl-transferase in melon fruit (Cucumis melo L.) ‘Hikapel’. Biodiversitas 21: 3041-3046. Melon (Cucumis melo L.) is one of the horticulture commodities that have high economic value and its needs increase continuously. Many new melon cultivars have been assembled to produce a higher quality melon. Melon 'Hikapel' developed by the Laboratory of Genetics and Breeding, Faculty of Biology UGM has distinctive character in the form of a strong aroma. This aroma is a complex mixture of various kinds of volatile compound. One of the main determinant compounds is a volatile ester, synthesized by the alcohol acyl-transferase enzyme encoded by the Cm-AAT1 gene. Characterization of Cm-AAT1 began with isolation of melon rinds to get total RNAs. Synthesis cDNA was conducted with oligo-dT primer, followed by detection of Cm-AAT1 using specific primers. A specific band was sequenced to perform phylogenetic tree. Gene expression from 4 melon cultivars, ‘Hikapel’, ‘Hikadi’, ‘Sun Lady’, and ‘Luna’ analysis was performed using relative quantitative Real-Time PCR. The results of this study showed that Cm-AAT1 owned not only by aromatic cultivars ‘Hikapel’ and ‘Hikadi’, but also owned by non-aromatic cultivars ‘Sun Lady’ and ‘Luna’. Phylogenetic analysis shows a high similarity between Cm-AAT1 on 'Hikapel' and 'Hikadi'. Gene expression analysis on 'Hikapel' increases as the process of fruit ripening during the storage period and it is in contrast to 'Hikadi' at decrease when the fruit began to enter the decay process on day 7th. Expression of Cm-AAT1 on ‘Hikapel’ was higher than ‘Hikadi’ at the peak of fruit maturity.